The Role of Notaries in Consumer Protection in E-Commerce in the Era of Digitalization - Ekaningsih, Lailasari; Hutomo, Irfan Rizky (Sultan Agung Notary Law Review, 2024)
Electronic commerce relies on the trust of commercial entities that guarantee the security of data and the legitimacy of transactions carried out. The government has enacted Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, one of which is to regulate electronic transactions. The ITE Law defines electronic transactions as activities that use electronic devices such as computers, internet networks and other digital media. The basic principle of electronic transactions is trust. To foster trust, stakeholders must strive for protection, especially consumer protection. In electronic transactions, there is an imbalance between economic actors and consumers in terms of bargaining power, which can result in legal agreements that are detrimental to consumers. In addition, storing consumer data as big data on computing systems does not guarantee its security, which can easily be lost, which is commonly referred to as a violation of consumer privacy. Consumers also need to be protected through education on the legal aspects of electronic transactions related to transaction terms, transaction security, transaction legality and dispute resolution. In fact, consumer protection in the field of electronic transactions is not yet optimal because several laws and regulations still contain inconsistencies and do not cover all aspects of protection.